Influence of Intraoperative Pain Management on Postoperative Delirium in Elderly Patients: A Prospective Single-Center Randomized Controlled Trial - Yuhao Du; Jiangbing Cao; Chen Gao; Keqiang He; Sheng Wang (Pain and Therapy)
Abstract Introduction Intraoperative analgesia and sedation are closely related to postoperative delirium. Depth of sedation based on bispectral index (BIS) guidance has been shown to reduce the occurrence of postoperative delirium (POD). However, the correlation between intraoperative analgesia levels and POD is unclear. The aim of this study was to investigate the effect of intraoperative analgesic management guided by the nociceptive stimulus index (NOX) on postoperative delirium. Methods In this prospective single-center randomized controlled study, elderly patients aged 65 and above, who are scheduled to undergo unilateral total knee arthroplasty (TKA), were allocated into two groups: the routine monitoring group (group R), which solely monitored patient sedation levels using BIS; and the NOX monitoring group (group N), which monitored patient analgesic levels using NOX based on BIS-monitored sedation levels. The primary outcome was the incidence of postoperative delirium within 3 days after surgery, using the confusion assessment method (CAM). Results From May 2022 to December 2022, a total of 240 patients were randomized; 12 were excluded because of failure to meet experimental conditions or were lost to follow-up. Patients in group N had a lower incidence rate (%) of POD on the first day compared to those in group R (8 (7%) vs 18 (16%), P = 0.041). The dosage of remifentanil administered in group N was significantly higher than that in group R (927.07 ± 268.09 vs 882.32 ± 187.91 mg, P = 0.002). Conclusions Appropriate intraoperative analgesia guided by NOX is associated with POD. When sedation levels were consistent, the incidence of POD was significantly reduced in older patients with NOX-guided analgesic management during unilateral TKA surgery.